The Durrells in Corfu. The complete second season - Barron, Steve, 1956-; Hall, Edward, 1966-; Hawes, Keeley, 1976-; O'Connor, Josh; Parker, Milo; Durrell, Gerald, 1925-1995; Durrell, Gerald, 1925-1995; Durrell, Gerald, 1925-1995. ([Place of publication not identified] : [publisher not identified], 2017)
Widow Louisa Durrell decides to leave 1930s England, relocating to the Greek island of Corfu, in hopes of a better life for her children.
Based on "The Corfu trilogy" by Gerald Durrell.
Anamorphic wide screen 1.77:1.
Features: Day in the life, Gerry and the animals, Going to market:, series 1 recap.
Keeley Hawes, Josh O'Connor, Milo Parker, Daisy Waterstone, Callum Woodhouse.
Originally broadcast on television in 2017.
TV rating: TV-PG.
Keywords: Durrell, Gerald, -- 1925-1995 -- Drama; Durrell, Gerald, -- 1925-1995 -- Homes and haunts -- Greece -- Corfu Island -- Drama; Durrell, Gerald, -- 1925-1995 -- Television adaptations; Zoologists -- Great Britain -- Biography -- Drama; Corfu Island (Greece) -- Drama; Television series; Fiction television programs; Video recordings for the hearing impaired; Based on the book; Biographical television programs